The Impact of Economic and Social Variables on ASEAN Logistics Performance - Yayik Masuarah; Indra Suhendra; Umayatu Suiroh Suharto (Universitas Negeri Malang, 2021)
The research to understand variable influence economic and social variables which include investment, port infrastructure, and labour on the Logistics Performance Index (LPI) in ASEAN countries. The decider of the sample is based on Crossection and Time series data of eight countries in ASEAN on the 2015-2018 period. Source of research data were obtained from the World Bank and International Monetary Fund (IMF). This study uses panel data analysis method with a fixed-effect model. Based on the results of the partial test (t-test), the investment variable showed a positive effect on the Logistics Performance Index (LPI). While for Labor and Economic Stability are negative effects on the Logistics Performance Index (LPI). And port infrastructure is no effect on the Logistics Performance Index (LPI). Also, based on simultaneous results (F-Test) indicates investment, port infrastructure, labour and economic stability have a significant effect on the Logistics Performance Index (LPI) in ASEAN countries on 2015-2018.